Carbon emission and financial development under the “double carbon” goal: Considering the upgrade of industrial structure - Yang, Wen-Jie; Tan, Meng-Zhuo; Chu, Shun-Ho; Chen, Zhen (Frontiers in Environmental Science, 2023)
Economic growth is fueled by financial development, which also takes the initiative in attaining green development and a low-carbon economy. The advanced industrial constitution is used as a moderator and mediator variable in this article to investigate whether there is a moderating effect and mediating effect between financial development and carbon emissions. This article chooses panel data from 283 Chinese cities from 2006 to 2019 to empirically analyze the impact of financial development on carbon emissions. The consequences indicate that financial development wields an evident active influence over carbon emissions. Additionally, the upgrading of industrial structures wields an evident positive impact on carbon emissions. There exists a medium impact of industrial structure upgrading. Results show that, first, when estimating carbon emissions demand, China’s financial expansion should be taken into consideration as a significant driver of rising carbon emissions. Second, although the extent of financial intermediation has a greater impact on carbon emissions than other financial development indicators, its effectiveness appears to have far less impact, even if it statistically has the potential to affect carbon emissions. Third, although the size of China’s stock market has a substantially greater impact on carbon emissions, the impact of its efficiency is quite little.